Pengaruh Brand Image dan Sikap Hedonis Terhadap Minat Beli Photocard K-Pop Melalui Korean Wave Sebagai Variabel Intervening (Studi Kasus Pada Member G.O Enhypen Indonesia) - Armansya, Ryza Maula; Widarko, Agus; Mustapita, Arini Fitria (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was conducted to analyze the influence of Brand Image and Hedonic Attitude towards K-Pop photocard buying interest through Korean Wave as intervening variables. This research used a type of causal associative research with a quantitative approach. The source of data is primary data derived from questionnaire distribution data at G.O Enhypen Indonesia and secondary data derived from documents, journals, previous researchers and other sources. The sampling technique in this study used the slovin formula which obtained a total of 82 samples with the questionnaire distribution method using the Likert scale. The data were analyzed using multiple linear regression measured using SPSS. Hypothesis testing using t-test. The results showed that brand image and hedonic attitude affect buying interest. Partial brand image and hedonistic attitude Positively affect buying interest. Brand image has a positive and insignificant effect on buying interest through the Korean wave. While hedonic attitudes have a positive and significant effect on buying interest through the Korean wave. Keywords : Brand Image, Hedonic Attitude, and Korean Wave